2021
DOI: 10.1177/00202940211003938
|View full text |Cite
|
Sign up to set email alerts
|

Task failure prediction for wafer-handling robotic arms by using various machine learning algorithms

Abstract: Industries are increasingly adopting automatic and intelligent manufacturing in production lines, such as those of semiconductor wafers, optoelectronic devices, and light-emitting diodes. For example, automatic robot arms have been used for pick-and-place workpiece applications. However, repairing automatic robot arms is time-consuming and increases the downtime of equipment and the cycle time of manufacturing. In this study, various machine learning (ML) models, such as the general linear model (GLM), random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Recent studies have investigated the problems related to position uncertainties of robotic arms end effectors and analyzed the life cycle of the robotic arm to improve the reliability of the wafer handling robot [2,3]. However, in general, planar translation of end effectors has been measured using only 2D imaging; with depth information missing, 6DOF localization of end effectors cannot be realized.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have investigated the problems related to position uncertainties of robotic arms end effectors and analyzed the life cycle of the robotic arm to improve the reliability of the wafer handling robot [2,3]. However, in general, planar translation of end effectors has been measured using only 2D imaging; with depth information missing, 6DOF localization of end effectors cannot be realized.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that the LSTM network could approximate the relationship between the input and output of a GNSS-integrated navigation system (INS) with high precision. In [ 14 ], a visual recognition system was combined with an artificial-intelligence machine-learning neural network to predict the maximum pick-and-place offset of a robot arm in the next minute. The developed LSTM model made predictions with high accuracy and reliability and met handling robot needs.…”
Section: Introductionmentioning
confidence: 99%